XRCC2 mutation causes premature ovarian insufficiency as well as non‐obstructive azoospermia in humans. Issue 3 (29th November 2018) - Zhang, Ya‐Xin; Li, Hai‐Yu; He, Wen‐Bin; Tu, Chaofeng; Du, Juan; Li, Wen; Lu, Guang‐Xiu; Lin, Ge; Yang, Yongjia; Tan, Yue‐Qiu
Abstract :